K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 12 2020

\(C=\frac{9x^2-16}{3x^2-4x}=\frac{\left(3x-4\right)\left(3x+4\right)}{x\left(3x-4\right)}=\frac{3x+4}{x}\)

\(D=\frac{2x-x^2}{x^2-4}=\frac{-x\left(x-2\right)}{\left(x-2\right)\left(x+2\right)}=\frac{-x}{x+2}\)

23 tháng 12 2020

Bài làm 

\(C=\frac{9x^2-16}{3x^2-4x}=\frac{\left(3x-4\right)\left(3x+4\right)}{x\left(3x-4\right)}=\frac{3x+4}{x}\)

\(E=\frac{2x-x^2}{x^2-4}=\frac{x\left(2-x\right)}{\left(x-2\right)\left(x+2\right)}=\frac{-x}{x+2}\)

2 tháng 4 2020

Là ông thọ

30 tháng 9 2016

Bài 2

a) 4x(x-3)-3x+9

=4x(x-3)-3(x-3)

= (x-3)(4x-3)

b) x3+2x2-2x-4

=(x3+2x2)-(2x+4)

=x2(x+2)-2(x+2)

=(x+2)(x2-2)

c) 4x2-4y+4y-1

=4x2-1

=(2x-1)(2x+1)

d) x5-x

=x(x4-1)

=x(x2-1)(x2+1)

31 tháng 10 2018

a) 4x(x-3)-3x+9

= 4x(x-3) - 3(x-3)

= (x-3)(4x-3)

b)x3 + 2x2 - 2x - 4

= x2(x + 2) - 2(x + 2)

= (x+2)(x2-2)

c) 4x2 - 4y +4y -1

= [(2x)2-12] + (-4y+4y)

= (2x+1)(2x-1)

d) x5-x

= x(x4 - 1)

Bài 1:

a: \(A=3\left(x^2-2x+1\right)-\left(x^2+2x+1\right)+2\left(x^2-9\right)-\left(4x^2+12x+9\right)-5+20x\)

\(=3x^2-6x+3-x^2-2x-1+2x^2-18-\left(4x^2+12x+9\right)-5+20x\)

\(=4x^2-8x-16-5+20x-4x^2-12x-9\)

\(=-30\)

b: \(B=5x\left(x^2-49\right)-x\left(4x^2-4x+1\right)-\left(x^3+4x^2-246x\right)-175\)

\(=5x^3-245x-4x^3+4x^2-x-x^3-4x^2+246x-175\)

\(=-175\)

d: \(D=25x^2-20x+4-36x^2-12x-1+11\left(x^2-4\right)-48+32x\)

\(=-11x^2-32x+3-48+32x+11x^2-44\)

=-89

19 tháng 6 2018

1) \(=9x^2-1\)

2) \(=9x^4-y^2\)

3)\(=25x^2-\dfrac{9}{4}\)

4) \(=x^3-1\)

5) \(=x^6-8\)

6) \(=x^3-64\)

7) \(=27x^3+8\)

8) \(=x^3-64\)

9) \(=x^3-\dfrac{1}{27}\)

10) \(x^3+\dfrac{1}{27}\)

31 tháng 12 2019

a) (2x - 1)(3x + 5) - 2(-4x + 1)2 = 6x2 + 10x - 3x - 5 - 2(16x2 - 8x + 1) = 6x2 - 3x - 5 - 32x2 + 16x - 2 = -26x2 + 13x - 7

b) \(\frac{x^2-16}{4x-x^2}=\frac{\left(x-4\right)\left(x+4\right)}{-x\left(x-4\right)}=-\frac{x+4}{x}\)

c) \(\frac{2x-9}{x^2-5x+6}+\frac{2x+1}{x-3}+\frac{x+3}{2-x}\)

\(\frac{2x-9}{x^2-2x-3x+6}+\frac{\left(2x+1\right)\left(x-2\right)}{\left(x-3\right)\left(x-2\right)}-\frac{\left(x+3\right)\left(x-3\right)}{\left(x-3\right)\left(x-2\right)}\)

\(\frac{2x-9+2x^2-3x-2-x^2+9}{\left(x-3\right)\left(x-2\right)}\)

\(\frac{x^2-x-2}{\left(x-3\right)\left(x-2\right)}\)

\(\frac{x^2-2x+x-2}{\left(x-3\right)\left(x-2\right)}\)

\(\frac{\left(x+1\right)\left(x-2\right)}{\left(x-3\right)\left(x-2\right)}=\frac{x+1}{x-3}\)

d) (x - 1)3 - (x + 1)3 + 6(x + 1)(x - 1)

= (x - 1 - x - 1)[(x - 1)2 + (x - 1)(x + 1) + (x + 1)2] + 6(x2 - 1)

= -2(x2 - 2x + 1  + x2 - 1 + x2 + 2x + 1) + 6x2 - 6

= -2(3x2 + 1) + 6x2 - 6

= -6x2 - 2 + 6x2  - 6

= -8

e) (2x + 7)2 - (4x + 14)(2x - 8) + (8 - 2x)2

= (2x + 7)2 - 2(2x + 7)(2x - 8) + (2x - 8)2

= (2x + 7 - 2x + 8)2

= 152 = 225